Strategi pengelolaan lingkungan ekowisata Sungai Gelombang di Desa Sipungguk Kecamatan Salo Kabupaten Kampar - Ari Prima Dewi; Ridwan Manda Putra; zulkarnain zulkarnain (Pelantar Press, 2023)
Sungai Gelombang Ecotourism located in Sipungguk Village, Salo District, Kampar Regency, Riau Province which has the potential to be developed as an environmentally ecotourism. This study aims to analyze the existing conditions of the Wave River ecotourism environment and determine the right strategy in managing the Wave River ecotourism environment. The research was conducted from October 2022 to January 2023. Primary data were obtained through questionnaires, direct observation in the field, documentation and in-depth interviews with the community, visitors and stakeholders, as well as secondary data obtained from references related to ecotourism environmental management. Data were analyzed using SWOT analysis. The results of the analysis show that the existing conditions of the Sungai Gelombang ecotourism ecology which includes rainfall, current, brightness, river area, color, depth, water temperature, pH, water bottom, vegetation, and biota are included in normal conditions that support ecological functions, Existing economic, socio-cultural, and institutional conditions show the need to increase the role of the surrounding community and government. Based on the SWOT analysis of Sungai Gelombang ecotourism management with the S-O (Strength - Opportunity) strategy. The strategy is to increase the role of the surrounding community and government with programs that support environmental conservation